Space and moral degeneration in Comida para perros, by Alejandro Cuevas (XXI Century. Spanish Literature and Culture, 2012)
Alejandro Cuevas is one of the most important writers of  the present narrative in Valladolid. Comida para perros is his first novel, which is written in an unaffected  style so that it is very suitable for an adolescent public. In this article we’re going to study the treatment of the space in the novel. The main character is a resentful teacher who don’t find any comprension in any of the spaces where his life happens. The main spheres of this novel are the house, the school, the mental hospital, and  the space of the street too. All these spheres are configurated, not with detailed descriptions, instead they are configurated with the negative relationships that the main character support with these spaces and with the rest of the characters of the novel. The school and the house are related with the frustration and the confinement, both aspects characteristic of our modern society. In the house, the bedroom is a space where the teacher degenerate in the moral corruption; on the other hand, in the school he suffers the bad treatment and the understanding by the bad mannered pupils and by another teachers. The space of the mental hospital is positive becasuse the main character, for the first time in his life, feels happy in a space where he find a connection with the rest of the mad people.
Keywords: Comida para perros; Alejandro Cuevas; space; moral corruption; degeneration; confinement; frustration